Dendrite-Free Li Metal Plating/Stripping Onto Three-Dimensional Vertical-Graphene@Carbon-Cloth Host - Yan, Congcong; Xu, Tingting; Ma, Caiyun; Zang, Jinhao; Xu, Junmin; Shi, Yumeng; Kong, Dezhi; Ke, Chang; Li, Xinjian; Wang, Ye (Frontiers in Chemistry, 2019)
Lithium metal is deemed as an ideal anode material for next generation lithium ion batteries (LIBs) due to its high specific capacity and lowest redox potential. However, uncontrolled lithium dendrite formation during electrochemical deposition leads to a low Coulombic efficiency and serious safety issues, dragging metallic lithium anodes out of practical application. One of promising strategies to suppress lithium dendrite issues is employing a three dimensional host with admirable conductivity and large surface area. Herein, a vertical graphene nanosheet grown on carbon cloth (VG/CC) synthesized is adopted as the Li deposition host. The three-dimensional VG/CC with a large surface area can provide abundant active nucleation sites and effectively reduce the current density, leading to homogeneous Li deposition to overcome dendrite issue. The Li@VG/CC anode exhibits a dendrite-free morphology after long cycle and superior electrochemical performance than that of planar Cu current collector. It delivers a small voltage hysteresis of 90.9 mV at a high current density of 10 mA cm-2, a Coulombic efficiency of 99% over 100 cycles at 2 mA·cm-2. Our results indicate that this all carbon based nanostructure host has a great potential for next generation Li metal batteries.